Ultrasound-Guided Regional Anesthesia Tutorial - Martha Johnson; Ben Swoboda (Association of American Medical Colleges, 2012)
Abstract This web-based tutorial was designed to provide a resource for learning about ultrasound-guided regional anesthesia. This project was the result of one resident's desire to have a resource where one could easily find all that is needed to know to prepare for a block. It is intended for novice learners, but also serves as a quick reference for the advanced practitioner. Our tutorial begins with an in-depth look at the brachial plexus. We then provide instruction modules for six common blocks-interscalene, supraclavicular, infraclavicular, axillary, femoral, and sciatic. We include detailed information on the lumbosacral plexus. Each module contains information about relevant anatomy, indications for the block, instructions on how to perform the block, ultrasound images and video, clinical pearls, risks and benefits, and current topical information from the regional anesthesia literature. There are other websites that are helpful for the regional anesthesia learner/practitioner, however this resource is unique in its content which includes not only technique, but also relevant anatomy, indications, risks and benefits, and current literature review. All of this is presented in a user-friendly format. A provided video adds a real time view of actual blocks being performed. There is a large constituency of anesthesiologists who would like to learn or improve their existing techniques for regional anesthesia and this resource will help them. It has already been used as a training tool for University of Washington Anesthesiology residents and fellows and has been met with uniform excitement and enthusiasm. Learners appreciate the graphics and video as well as the informational content which is "enough but not too much."